Antibiotic-Resistant Lactic Acid Bacteria Pediococcus acidilactici Isolated from Buffalo’s Milk Fermentation (Dadiah) Bukittinggi, West Sumatera - Dewi, Nadia Purnama; Abdullah, Dessy; Pratama, Yudha Endra (Universitas Labuhanbatu, 2024)
The use of antibiotics is still carried out in the health world so that it will cause a big problem, namely antibiotic resistance. The use of antibiotics has also been limited but cannot be stopped. The use of probiotics as therapy in the world of health is increasing every year, so it is necessary to study the combination of antibiotics and probiotics so as not to reduce the effectiveness of probiotics later. This study aims to determine the resistance ability of lactic acid bacteria (LAB) isolates from Buffalos Milk Fermentation (called as dadiah) Bukittinggi against antibiotics. This research uses a descriptive, experimental method where the observations made are related to the total mass of isolates per ml and the clear zone of LAB isolates from dadiah Bukittinggi against antibiotics. In this study, five types of LAB isolates from dadiah Bukittinggi were used, and it was found that the total mass of isolates ranged from 4-194 x108 CFU/ml. In addition to antibiotic resistance, it was known that dadiah LAB isolates resisted Kanamycin and Penicillin by 75%. While on the antibiotic chloramphenicol, ampicillin and tetracyclin, the four isolates are suspect to the antibiotic. The five LAB isolates of dadiah used in the study, DS1 isolate had the best total mass and was resistant to kanamycin and penicillin